Assessing the Stock Market Performances of EU Low-Cost Airlines - Barrows, Samuel D. (International Journal of Economics and Financial Issues, 2019)
The top seven Low-Cost Airlines in the EU, as ranked by 2018 passenger travel, are evaluated over a four year time frame using stock market performance in order to ascertain which airlines provide superior performance in relation to the others in the group and in relation to the European stock market. Several topics are discussed relating to this group of airlines including business models, operating strategies, airline networks, regional airports, and standardized fleets. Three airlines emerge with superior stock market performance: Jet2, WizzAir, and Ryanair. Keywords: EU; Low-Cost Airlines; Stock Market Performance JEL classifications: G11; L93; R40 DOI: https://doi.org/10.32479/ijefi.8160